Electrical, mechanical, and thermal analysis of natural rubber/polyaniline-DBSA composite - Silva, Michael Jonas da [UNESP]; Sanches, Aléx Otávio [UNESP]; Malmonge, Luiz Francisco [UNESP]; Malmonge, José Antonio [UNESP] (Univ Fed Sao Carlos, Dept Engenharia Materials, 2014)
A composite of natural rubber (NR) with polyaniline (PANI) was obtained by mixing an aqueous dispersion of dodecylbenzenesulfonic acid (DBSA)-doped PANI with NR latex in different concentrations. Films were obtained by the casting method and characterized by ultraviolet visible near-infrared (UV-Vis-NIR) spectroscopy, thermogravimetry/differential thermogravimetry (TG/DTG), stress-strain testing, differential scanning calorimetry (DSC), and DC electrical conductivity measurements. The UV-vis-NIR spectrum showed that PANI remained doped in the composite, and this improved the mechanical and electrical proprieties of NR films and afforded them good thermal stability up to similar to 200 degrees C. The percolation threshold did not follow the universal critical exponent, and in this case, conduction preferentially occurs by hopping and tunneling.
Keywords: Natural rubber; Polyaniline; Electrical conductivity; Percolation threshold